Funnel control for nonlinear systems with higher relative degree. Issue 1 (17th December 2018) - Berger, Thomas; Lê, Huy Hoàng; Reis, Timo
Abstract: We consider tracking control for nonlinear multi‐input, multi‐output systems which have arbitrary strict relative degree and input‐to‐state stable internal dynamics. For a given reference signal, our aim is to design a controller which achieves that the tracking error evolves within a prespecified performance funnel around the reference signal. To this end, we introduce a new controller which involves the first r−1 derivatives of the tracking error, where r is the strict relative degree of the system.